Transportation Mobile Applications Adoption Behavior Does Affect Overseas Residents' Life Satisfaction: Involvement as A Moderator - Nargis Dewan; Md Billal Hossain; Gwi-Gon Kim; Anna Dunay; Csaba Bálint Illés (Cogent Business & Management, 2022)
Mobile application acceptance is an emerging research area that gained wide-spread popularity. Managerially important but the overlooked aspect is mobile applications adoption effect on overseas resident's life satisfaction. Travel applications make users' life easier with a smooth travel satisfaction that contributes to life satisfaction. The users who perceive applications useful and easy to use are satisfied with life in South Korea. Moderating effects of travelers' involvement between three types of transportation applications and perceived usefulness and ease of use, where people use mobile applications before and during traveling, to fulfill travel needs, location detail, and to make the right arrangements were identified as moderator of technology adoption model (TAM). Data collected from 400 users conclude that relation of usefulness with travel satisfaction is not significant while residents perceive ease of use were significant determinants of travel satisfaction. TAM acceptance influences travel satisfaction which provides more feeling too satisfied from life.
Keywords: 650; Mobile travel application; perceived ease of use; perceived usefulness; traveler involvement; traveler satisfaction